An energy-consumption model for establishing an integrated energy-consumption process in a machining system. Issue 6 (1st November 2020) - Gu, Wenbin; Li, Zhuo; Chen, Zeyu; Li, Yuxin
ABSTRACT: Manufacturing industry accounts for a significant part of world's energy consumption and environmental pollutions. Machining process is a major process of manufacturing industries, plays an important role in energy saving and emission reduction. This paper established an energy-consumption model for machining processes considering the full states of machining processes. Firstly, machining processes are decomposed into activities and activity transitions according to the different characteristics of energy demand. Secondly, based on the decomposition of activities and activity transitions, the energy-consumption models of activities and activity transitions are established, respectively. Thirdly, combining with the established energy-consumption models of activities and activity transitions, this paper proposes an energy-consumption model for the entire machining processes that systematically reflects different machining states. Finally, the simulation results show that the proposed model can accurately calculate the energy consumption of machining processes and provide guidance for machine tool energy saving.